Modeling gene dosage compensation mediated by sensor loops in large-scale mathematical models of microRNA-transcription factor networks - Acón Chan, Man Sai (2018)
In a previous work we developed a biocomputational platform to automatically construct mathematical models of microRNA-transcription factor (TF) regulatory network to study gene dosage compensation. We hypothesized that gene dosage compensation maintains the viability of tumoral cells with high levels of chromosomal alterations by down regulating the expression of a core group of compensated genes. Here we report that those compensated candidates form clusters according to their chromosomal locations and they share the connections of a large-scale network of putative interactions with miRNAs and TFs. Although initial models of feed-forward loops do not show gene dosage compensation, we simplified the model by including only sensor loops of experimentally validated interactions. A sensor loop allows a gene to sense and react to fluctuations of its own expression. The resulting model shows gene dosage compensation for MYC and STAT3 but the genetic regulation of these two genes can be extended to co-regulate the expression of other compensated genes. These results contribute to the identification of a network of gene dosage compensation, which manipulation of specific nodes has the potential to become a novel approach to specifically target aneuploid cancer cells.